Gender equality knowledge analysis for sexual violence prevention among adolescents in the ADEM community - Pangalila Ndoen, Daisy; Al Uyun, Dhia; Wahyuningsih, Sri (Wacana Journal of Social and Humanity Studies, 2026)
Objective: Gender equality is a key component of the Sustainable Development Goals (SDGs), particularly in addressing gender-based violence and ensuring equal access to education, skills development, and economic opportunities. This study aimed to analyze gender equality knowledge related to sexual violence within the ADEM Community in Batu City, with a focus on Papuan adolescents. Design/Methods/Approach: Despite extensive research on gender equality and sexual violence prevention among adolescents, limited studies have examined the application of gender equality knowledge using a psychosocial approach in the ADEM community context. A descriptive quantitative design was employed involving 93 respondents. Data were analyzed using mixed-methods, polynomial regression, Principal Component Analysis (PCA), and Pearson correlation analysis to identify dominant knowledge components and relationships among variables. Instrument validity was assessed using t-tests, and reliability testing was conducted. Findings: Most respondents, both male and female, demonstrated a good level of knowledge about gender equality. Pearson correlation analysis revealed a very strong association between male and female knowledge levels (r = 0.875; p = 0.022) and a strong correlation with the good knowledge category (r > 0.95). Originality/Value: Gender awareness in the ADEM community is evenly distributed across genders, providing a shared foundation for sexual violence prevention. Practical/Policy implication: These results suggest that gender equality knowledge within the ADEM community is relatively balanced across genders and may contribute to efforts aimed at preventing sexual violence among adolescents.   Keywords:  Gender equality knowledge; sexual violence prevention; adolescents; ADEM program; gender awareness JEL Classification: J16; I24; Z13